Hydrolytic Degradation and Erosion of Polyester Biomaterials - Woodard, Lindsay N; Grunlan, Melissa A (ACS macro letters, 2018)
Strategies to refine the degradation behavior of polyester biomaterials, particularly to overcome the limitations of slow hydrolytic degradation, would broaden their utility. Herein, we examine the complexities of polyester degradation behavior, its assessment, and strategies for refinement. The factors governing polyester degradation are strikingly complex. In addition to the half-life of the hydrolytically labile bond, a series of interdependent material properties must be considered. Thus, methods used to characterize such material properties, both before and during degradation, must be carefully selected. Assessment of degradation behavior is further complicated by the variability of reported test protocols and the need for accelerated rather than real-time in vitro testing conditions. Ultimately, through better control of degradation behavior and correlation of in vitro, simulated degradation to that observed in vivo, the development of superior devices prepared with polyester biomaterials may be achieved.